ANALISIS KEPUASAN KONSUMEN TERHADAP PRODUK ROKOK DJARUM SUPER MLD DI KALANGAN ANAK MUDA - Bernik, Merita; Dwi Putra, Aldy Gustian (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2019)
Today's development requires young people in Bandung to follow a lifestyle. Cigarettes are one product that can show a person's lifestyle. Although it has been socialized that cigarettes are not good for health, but because of the demands of lifestyle and influenced by relationships, many young people in the city of Bandung smoke. Many cigarette companies in Indonesia are famous for producing cigarettes that have a distinctive taste. In the research, the level of consumer satisfaction was measured by analyzing the marketing mix indicator on Djarum Super MLD cigarette products among young people in the city of Bandung. The method of this research is descriptive method that using primary data in the form of interviews, observation and questionnaires, and also used secondary data. The smpling technique used is purposive sampling, which is a sample of young people over the age of 20 years. The results show that the level of consumer satisfaction in the city of Bandung on Djarum Super MLD cigarette products is at a good level or it can be stated that consumers are satisfied with product of Djarum Super MLD cigarette.